MOTILITY DISFUNCTION OF THE BILIARY SYSTEM IN CONVALESCENTS OF VIRAL HEPATITIS A AND B, METHODS OF CORRECTION - T. O. Daminov; L. N. Tuychiev; G. K. Khudaykulova; F. Sh. Mamatmusaeva; L. Yu. Aladova; G. N. Sobirova (LLC "Diagnostics and Vaccines", 2015)
The results of studies of changes in motor function of the biliary system in convalescent children after hepatitis A virus (rHAV) and B (rHBV ) characterized by disorders of the biliary system are presented in the article. Children who have suffered HAV and HBV display a variety of pathologic and pathophysiologic changes conditioned by various hepatitis viruses. The combination of diet therapy, drug-free (physiotherapy) and medication (Phosphogliv) interventions contributes to the overall normalization of the function of the biliary tract in all children who have suffered HAV. The same is true about the majority of convalescent children after HBV. This allows the authors to recommend the complex of interventions as the optimal approach to the rehabilitation of children who have suffered viral hepatitis.